2013
DOI: 10.1162/rest_a_00237
|View full text |Cite
|
Sign up to set email alerts
|

HIV Status and Labor Market Participation in South Africa

Abstract: for especially helpful comments and suggestions. Levinsohn acknowledges support from the NICHD. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
(24 reference statements)
1
26
1
1
Order By: Relevance
“…Some of these studies have examined the household-level consequences of adult mortality due to HIV/AIDS [8, 9], whereas others have employed cross-sectional data to describe socio-economic characteristics of HIV-infected individuals and to compare them to HIV-uninfected individuals and their households [10]. A few studies have also used longitudinal or retrospective data to examine how socio-economic outcomes change as a result of HIV disease progression [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have examined the household-level consequences of adult mortality due to HIV/AIDS [8, 9], whereas others have employed cross-sectional data to describe socio-economic characteristics of HIV-infected individuals and to compare them to HIV-uninfected individuals and their households [10]. A few studies have also used longitudinal or retrospective data to examine how socio-economic outcomes change as a result of HIV disease progression [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…McLaren (2011) found that in South Africa, individuals with HIV tend to be unemployed, and unemployed people are more likely to be HIV positive. Furthermore, Levinsohn et al (2011) found that being HIV-positive is associated with a 6 to 7% point increase in the likelihood of being unemployed. Table 3 shows that about 56 (92%) of patients had disclosed their HIV status to someone and only 4 (7%) had not disclosed their HIV status.…”
Section: Age In Years (Patients)mentioning
confidence: 99%
“…Los costos de buscar atención médica, combinados con ingresos reducidos, representan una carga económica significativa para muchos hogares en los PBI y los PIM. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Esta carga a menudo puede tener como resultado que los hogares recorten gastos esenciales, como la comida. 57 Los hogares pobres encabezados por mujeres son más vulnerables a la catástrofe económica como resultado de los eventos adversos de salud.…”
Section: -21unclassified